KAJIAN HIDRODINAMIKA EKSTRAKS1 CAIR-CAIR PADA KOLOM SIAN - Putranto, Adiya
Extraction is a separation method based on solubility difference of solute in solvent. Extraction hydrodynamics is an important factor that determines the amount of solute gained in extract phase because hydrodynamics influences mass transfer area (drops area formed in the column). In extraction operation, component dispersed is called dispersed phase and component flown continuosly is called continuous phase. A lot of experiments about liquid-liquid extraction have been conducted in Separation and Purification Laboratory in ITB. Hydrodynamics aspect in packing column is quite difficult due to the presence of packing materials. To analyze hydrodynamics aspect of packing column, we must analyze hydrodynamics aspect of single drop in spray column, single drop in packing column, multiple drops in spray column, and multiple drops in packing column. Hydrodynamics aspect of single drop in spray column can be assumed similar to hydrodynamics aspect of rigid sphere in low Reynold number, but in high Reynold number zone there is shape distortion of drop due to local force in surface area. Also, internal circulation and oscillation happen in high Reynold number zone. In certain condition, drop breaks into smaller drops. Hydrodynamics aspect of single drop in packing column is seldom studied. If single drop passes packing column, there are several possibilities of drop behavior. Drop can pass packing material freely, or can be distorted, or can break into smaller drops. Hydrodynamics aspect of multiple drops in spray column is more complex due to population aspect. Drop population is different for each stages, this population can be predicted from transport, breakage, and coalescence. By arranging drop population balance, we can determine average diameter, hold up, and solute concentration for each phase. The same as hydrodynamics aspect of multiple drops in spray column, hydrodynamics aspect of multiple drops in packing column is determined by transport, breakage, and coalescence. The difference between hydrodynamics aspect in spray column and packing column is there are more breakage and fewer coalescence happening in packing column. Hydrodynamics aspect in packing column is also influenced by packing wetting phenomena, type, and size of packing material. By studying hydrodynamics of multiple drops in packing column, we can design extraction column more accurately. Moreover, we can determine solute concentration in each phase from extraction column. This step is called rate process.